Dynamic Analysis of Epidemic Model for Cholera Disease Spreading with Quarantine - Husadaningsih, Tyas; K, Wuryansari Muharini; Imron, Aruman (Graduate School, Universitas Brawijaya, 2018)
In this paper, the epidemic model of cholera disease spreading by quarantine is discussed. It is assumed that the spread of cholera not only through direct contact between susceptible human populations with bacteria but also through direct contact between susceptible human populations with infected human populations and reduced bacterial populations not only die naturally but can also be done by means of extermination bacteria. Determination of equilibrium points, existence and local stability of equilibrium points are investigated. Numerical simulations are performed to illustrate the results of the analysis.Keywords: Cholera Disease, Epidemic Model, Runge-Kutta Method 4th order, Stability, Quarantine.